Application of the Tilawati Method in Improving The Quality of Reading the Qur'an for MDTA Students Nurul Huda Singajaya Indramayu - Mariya Ulfah (LECTURES: Journal of Islamic and Education Studies, 2022)
This research is to find out how the application of the tilawati method improves the quality of students reading the Koran at MDTA Nurul Huda Singajaya Indramayu. The type of this research is in the form of field research, namely research that is carried out systematically by collecting existing data in the field. And the research technique used is data analysis technique, namely the process of searching and systematically compiling data obtained from interviews, observation and documentation. The conclusion from this study is that the application of the tilawati method is carried out in 3 stages, the effectiveness of learning can be adjusted by several existing aspects. Then that in increasing the quality or results of improving the quality of Santri reading the Qur'an consists of several methods, teacher quality and child factors. The tilawati method applied at MDTA Nurul Huda Singajaya Indramayu is very effective in improving the quality of santri's reading of the Qur'an